The operator as a factor of success in ART restorations - Carolina da Franca; Viviane Colares; Evert van Amerongen (Universidade Estadual de Campinas, 2015)
Aim: To evaluate the operator as a factor of success in atraumatic restorative treatment (ART) restorations. Methods: This was a clinical intervention study. The sample consisted of 271 glassionomer cement (Ketac Molar, 3M ESPE) restorations placed in 246 children aged 5 to 9 years attending public schools in Recife, Brazil. The operators were two senior undergraduate dental students and one dentist, classified as 'inexperienced' and 'experienced', respectively. Two groups of children were formed: one treated by the undergraduate students and the other treated by the dentist. The evaluation of the restorations took place at 1, 4 and 12 months by three senior undergraduate dental students. Results: Comparing the operators, a significant difference was found in class II cavities filled by students, who had a lower rate of success. There were no differences between the dentist and undergraduate dental students for class I cavities. Conclusions: The operator's experience makes a difference in the success rate of more complex ART restorations when an experienced operator receives the same training as an inexperienced operator.